2001
DOI: 10.1095/biolreprod65.5.1403
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Deviation and Acquisition of Ovulatory Capacity in Bovine Follicles1

Abstract: Selection of dominant follicles in cattle is associated with a deviation in growth rate between the dominant and largest subordinate follicle of a wave (diameter deviation). To determine whether acquisition of ovulatory capacity is temporally associated with diameter deviation, cows were challenged with purified LH at known times after a GnRH-induced LH surge (experiment 1) or at known follicular diameters (experiments 2 and 3). A 4-mg dose of LH induced ovulation in all cows when the largest follicle was > or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
154
6
43

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(218 citation statements)
references
References 28 publications
15
154
6
43
Order By: Relevance
“…These differences could be attributed to speculation and therefore the different physiological statuses of the B. taurus breeds. In this breed, ovulation can be observed when the diameter of the follicle is close to 10 mm (Ginther et al 1996;Sartori et al 2001). Dairy cattle respond in different ways to eCG administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences could be attributed to speculation and therefore the different physiological statuses of the B. taurus breeds. In this breed, ovulation can be observed when the diameter of the follicle is close to 10 mm (Ginther et al 1996;Sartori et al 2001). Dairy cattle respond in different ways to eCG administration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, after injection of 400 or 600 IU of eCG, the growth rate and diameter of the ovulatory follicle were, respectively, 3.9±0.6 mm/day and 14.5±1.1 mm, and 3.5±0.5 mm/day and 13.9±1.2 mm (Ferreira et al 2013). It does not appear that a reduction in the diameter of the ovulatory follicle is a determining factor for infertility (Sartori et al 2001;Perry et al 2005) as long as a minimal value close to 10 mm is observed (Martinez et al 1999;Sartori et al 2001). Thus, in Senepol cattle (B. taurus) and Nelore cattle (B. indicus), ovulation of the follicle with a diameter less than 8.5 mm is considered as physiological (Sartori and Barros 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na etapa fi nal do processo que precede a ovulação, o crescimento folicular está associado à maturação do oócito e, consequentemente, a sua capacidade fecundante [18]. As relações entre o tamanho do FO, formação do corpo lúteo, a produção de progesterona e o desenvolvimento embrionário inicial estão associadas ao estabelecimento da prenhez em novilhas e vacas de corte [2,11,19].…”
Section: Introductionunclassified
“…Esses fatores podem ser explicados devido à ovulação de um oócito imaturo, que compromete a fertilização e sobrevivência embrionária, estando também associados à baixa produção e liberação de estradiol pelo FO [9,18]. O uso de eCG [1,6,12] ou FSH [16,17] no fi nal do tratamento para a sincronização do estro e da ovulação para IATF tem como objetivos: promover maior crescimento folicular, maior produção de estradiol e a maturação do oócito.…”
Section: Introductionunclassified